Assistance in the Management of NIB Lao Coffee Producers "Sobo Balek" Giripurno Village, Bumiaji District, Batu City Through Online Single Submission (OSS) - Sania Khoiri Rahma; Riski Ayu Anggreini; Widhy Rahmat Nazaryan (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Business legality is important to own by Micro, Small, and Medium Enterprises (MSME), but currently, there are still not many MSME actors who realize the importance of having legality for their businesses. This has resulted in many MSME actors not having business legality, one of which is the Kopi Laos “Sobo Balek” MSME. Management of business legality such as NIB can be done online through Online Single Submission (OSS). This community service activity aims to assist MSMEs starting by introducing, increasing knowledge, and registering to have a NIB. The method used in this activity consisted of 3 stages, namely observation, outreach, and mentoring. Implementation of activities includes sharing with MSMEs, obtaining business licenses, and submitting NIB. The result of this activity is that MSME partners gain knowledge about the importance of business legality, and the benefits and advantages that come from business legality. In addition, the MSME also succeeded in obtaining business legality in the form of a NIB. The recommended recommendation is to have further guidance to get a PIRT for Kopi Laos.